Ion temperature and toroidal velocity edge transport barriers in KSTAR. (6th July 2015) - Ko, Won-Ha; Ko, S.H.; Kwon, J.M.; Diamond, P.H.; Ida, K.; Jeon, Y.M.; Lee, J.H.; Yoon, S.W.; Kwak, J.G.
Abstract: The structure and evolution of the ion temperature ( ) and toroidal rotation ( ) profile have been investigated in neutral beam injection (NBI)-heated KSTAR H-mode plasmas, both without and with resonant magnetic pertubations (RMPs). A clear disparity between the width of the -pedestal and that of the -pedestal was observed. Also, it was found that there exists a close correlation and weak relative hysteresis between the pedestal and during both L → H and H → L transitions. During the L → H transition, the -pedestal is observed to form ahead of the -pedestal, and build inward from the separatrix. Linear gyrokinetic stability analysis of these KSTAR profiles was performed. The results indicate that parallel velocity shear is a relevant drive for pedestal turbulence and transport. This was largely ignored in previous studies of the pedestal micro-stability. Pedestal ion temperature and rotation profiles were also measured during edge localized mode (ELM) suppression experiments on KSTAR using an n = 1 RMPs. It was found that the top values of the ion temperature and toroidal rotation pedestal drop with RMPs when ELMs are suppressed.